MENTAL RESILIENCE IN EDUCATION: THE CASE OF GREEK HIGH SCHOOLS TEACHERS: Received: 2nd April 2021; Revised: 18th October 2021, 2nd December 2021; Accepted: 16th December 2021 - Kaltsas, Apostolos (PUPIL: International Journal of Teaching, Education and Learning, 2021)
The term “mental resilience” defines the ability of the individual to overcome any adversity and to continue to develop. It is part of the set of personality traits, as well as genetic traits with which a person is either born or acquired in infancy and/or childhood. Teachers play an important role in promoting students' mental health in creating a suitable and supportive environment for them, since with their support students can acquire skills that will enhance their self-image and self-confidence, thus helping them in their evolution and progress. This paper aims to investigate the mental resilience of high school teachers and how it correlates with gender, age, and years of service. The survey involved 29 teachers (18 men (62.1%) and 11 women (37.9%)) who served in high schools in the prefecture of Attica in Greece. The Connor-Davidson Resilience Scale (CD-RISC) was used to measure mental resilience. This questionnaire consists of 25 self-rated items with a 5-point scale from 0 (‘not true at all’) to 4 (‘true nearly all the time’) which correspond to five factors. The analysis of the results showed that the participants had high resilience, gender is correlated with “trust in one’s instincts” factor positively and statistically significant, years of service correlated with “control” factor positively and statistically significant, and with “personal tolerance” factor negatively and statistically significant. Age was found to be positive and statistically significantly correlated with the “control” factor. In conclusion, in the era of continuous development and change, mental resilience is important for the field of education as teachers play an important role in the lives of children facing difficulties while contributing to the promotion of collaborative school culture.